Pengaruh Tipe Kepemimpinan dan Religiusitas Orang Tua terhadap Preferensi Pemilihan Sekolah Dasar Anak Pasca-TK pada MI atau SD: Studi TK/RA Tarbiyatul Athfal PSM Tanjunganom Nganjuk - Setiawan, Eka Aprianto Nur; Wahjoedi, Tri; Lazuardi, Sofyan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study is motivated by the increasing parental indecision in determining children’s primary school placement after kindergarten, particularly between Madrasah Ibtidaiyah (MI) and public elementary schools (SD). Such decisions are influenced not only by academic considerations but also by parents’ religiosity and leadership types reflected in their educational decision-making styles. This study aims to analyze the effects of parental leadership types based on the DISC and Personality Plus frameworks, as well as parental religiosity, on parents’ preferences in selecting primary schools for their children after kindergarten at TK/RA Tarbiyatul Athfal PSM Tanjunganom. This research employed a quantitative approach with an explanatory research design using multiple linear regression analysis. Data were collected through questionnaires distributed to 57 parents of students at TK/RA Tarbiyatul Athfal PSM Tanjunganom. The results indicate that, partially, parental leadership based on the DISC model (X₁) has a positive and significant effect on school preference (Sig. 0.013 < 0.05), while leadership based on Personality Plus (X₂) does not show a significant effect (Sig. 0.856 > 0.05). Parental religiosity (X₃) demonstrates a positive and highly significant influence on primary school selection preference (Sig. 0.000 < 0.05). Simultaneously, the three independent variables contribute significantly to the model, with a coefficient of determination (R²) of 0.822, indicating that 82.2% of the variance in parents’ primary school selection decisions can be explained by the research model. These findings confirm that parental leadership and religiosity are dominant factors in educational decision-making at the primary school level.